Records of Copiatestes filiferus (Leukart, in Sars, 1885) Gibson and Bray, 1977 (Digenea) and Gorgorhynchus sp. (Acanthocepahala) of marine fish from peruvian coast - Tantaleán V, Manuel (2004)
In this paper, Copiatestes filiferus (Leukart, in Sars, 1885) Gibson and Bray, 1977 (Digenea) and Gorgorhynchus sp. (Acanthocephala) parasites of Hemilutjanus macrophthalmos (Teleostei), both parasites are new records from Peru and the fish is a new host.